2015
DOI: 10.1116/1.4913377
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a platform to isolate the influences of surface nanotopography from chemistry on bacterial attachment and growth

Abstract: Billions of dollars are spent annually worldwide to combat the adverse effects of bacterial attachment and biofilm formation in industries as varied as maritime, food, and health. While advances in the fabrication of antifouling surfaces have been reported recently, a number of the essential aspects responsible for the formation of biofilms remain unresolved, including the important initial stages of bacterial attachment to a substrate surface. The reduction of bacterial attachment to surfaces is a key concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…While the introduction of nanoscale topography (random spherical protrusions, R ∼100 nm) enhanced biomass accumulation on substrates with either terminal group, the structure of the adhered biomass on nanorough substrates were clearly dependent on surface chemistry. On the contrary, Pegalajar-Jurado et al reported no statistically significant difference between E. coli biomass on a smooth control and nanostructured surfaces (colloidal crystals, radius ∼200 nm, height ∼30 nm), for both hydrophobic (WCA = 90°) and hydrophilic (WCA = 37°) surfaces (Pegalajar-Jurado et al, 2015).…”
Section: Effect Of Topographical Scale On Bacterial Attachmentmentioning
confidence: 97%
“…While the introduction of nanoscale topography (random spherical protrusions, R ∼100 nm) enhanced biomass accumulation on substrates with either terminal group, the structure of the adhered biomass on nanorough substrates were clearly dependent on surface chemistry. On the contrary, Pegalajar-Jurado et al reported no statistically significant difference between E. coli biomass on a smooth control and nanostructured surfaces (colloidal crystals, radius ∼200 nm, height ∼30 nm), for both hydrophobic (WCA = 90°) and hydrophilic (WCA = 37°) surfaces (Pegalajar-Jurado et al, 2015).…”
Section: Effect Of Topographical Scale On Bacterial Attachmentmentioning
confidence: 97%
“…As the physical attributes of many devices are often optimal for their given application, much research directed toward reducing biofilm formation has been directed toward modification or adaptation of current device technology. For example, through modification via poly­(ethylene glycol), , topography, , zwitterions, increased microbicidal activity, , or a combination of these a reduction in bacterial attachment has been observed . Recently, a novel class of nontoxic bacterial antiadhesive materials have emerged that significantly reduce bacterial attachment and biofilm formation both in vitro and in an in vivo foreign body mouse infection model. These are polyacrylates, with monomers characterized by their weakly amphiphilic nature that reduce colonization of surfaces, and since they prevent biofilm formation rather than killing bacteria, minimize the selective pressure on bacteria to evolve antibiotic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In another work by Pegalajar-Juradoa et al, colloidal arrays and plasma polymerization technique were combined as a fabrication method to generate antibacterial surfaces without altering surface chemistry. This study suggests that bacteria prefer to adhere on the nanostructured hydrophilic regions [132].…”
Section: Anti-fouling Surface Structuresmentioning
confidence: 66%